Pharmacist Instruction of Physical Assessment for Pharmacy Students - Bolesta, Scott (American Journal of Pharmaceutical Education, 2011)
OBJECTIVE: To assess the impact of a change from nurse to pharmacist instructors and a new curriculum intended to encourage students’ use of physical assessment skills. DESIGN: Pharmacist faculty members redesigned the physical assessment curriculum to focus on those assessment skills most likely to be performed by practicing pharmacists. The 5 focus areas were general assessment skills, gastrointestinal system, pulmonary system, central and peripheral nervous system, and cardiovascular system. Instructional methods used included prelaboratory assignments, brief introductory lectures, demonstration of assessment techniques, application of techniques with a laboratory partner, and demonstration of competence using a mannequin. ASSESSMENT: A 16-item survey instrument was administered to determine students’ perceptions of the revised curriculum. Students who received instruction from pharmacist faculty members used their physical assessment skills more, especially during advanced pharmacy practice experiences (APPEs), than students who received instruction from nurse faculty members. Students instructed by pharmacist faculty members also felt more comfortable with their skills and rated the instruction as more practical. CONCLUSION: A redesigned curriculum and pharmacist-led instruction resulted in improved pharmacy student comfort with and use of physical assessment skills.